Actualización diagnóstica y terapéutica de la enfermedad de Kawasaki en niños menores de 5 años. - Mantilla Cadena, Ricardo David (2023)
Kawasaki disease is a rare pediatric condition that involves systemic inflammation in the body. The characteristic symptoms are persistent fever for at least five days, skin rash, bilateral conjunctivitis, changes in the mouth and lips, swelling of the hands and feet, and changes in the cervical lymph nodes. This research aimed to carry out a bibliographic review of the diagnostic and therapeutic update in children under five years of age with Kawasaki disease. For this, a basic, descriptive, and transversal research was carried out consisting of a bibliographic review of documents published in the last five years. A total of 84 documents were identified, of which 40 were used in the study. The information was obtained from regional and high-impact databases such as PubMed, Scielo, Elsevier, PubMed, Scopus, e- book Central, ClinicalKey, UpToDate, Latindex, Scielo, Lilacs, Medigraphic, Redalyc, Medline, Ice Web of Science, among other. As main results, the main diagnostic and therapeutic methods of Kawasaki disease are described, in order to establish early treatments to reduce the risk of serious cardiac complications. In patients with Kawasaki disease, the prognosis is usually favorable with timely diagnosis and treatment, but long-term cardiological follow-up is required. Kawasaki disease continues to be the subject of active research to understand its cause better and improve its management. That is why, in this work, aspects that promote research and monitoring of Kawasaki disease were analyzed.